The Role of Farmer Group Heads in the Adoption of Rice Paddy Cultivation Innovations in Rangdumulya Village - Fauziah Saraswati; Fatimah Azzahra; Muhamad Rom Ali Fikri (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2024)
Most farmers still need more efficient ways to increase the effectiveness of their farms. To allow farmers' farms to advance from before, it is essential to increase the role of farmer group heads in enhancing their capacity to adopt farming innovations. Interactions between farmers in the group create a flow of information exchange, forming a communication network. The study aimed to examine how the head of the farmer group affected the adoption of innovations in paddy rice cultivation in Rangdumulya Village and analyze the communication network in Gapoktan Karya Sentosa in Rangdumulya Village. The village was selected purposively. The study ran from January through April of 2024. With a population of 536 farmers, 42 respondents were selected from among the samples using proportional random sampling. The research's variables are the roles of farmer group leaders as motivators, communicators, organizers, facilitators, and innovators. Data analysis employed multiple linear regression analysis and sociometric analysis. The role of farmer group leaders as facilitators and innovators significantly and positively influences the adoption of paddy rice cultivation innovations. The communication network of Gapoktan Karya Sentosa shows that the actor who is most often the source of information for farmers is Mr. Jalaluddin because he is the head of Gapoktan. The results of identifying the role figures play in the Gapoktan Karya Sentosa's communication network show that Mr. Jalaluddin plays the opinion leader, and Mr. Jalaluddin plays the gatekeeper.